Quorum sensing in Pseudomonas savastanoi pv. savastanoi and Erwinia toletana: role in virulence and interspecies interactions in the olive knot - Caballo-Ponce, Eloy; Meng, Xianfa; Uzelac, Gordana; Halliday, Nigel; Cámara, Miguel; Licastro, Danilo; Passos da Silva, Daniel; Ramos, Cayo; Venturi, Vittorio; Kivisaar, Maia (American Society for Microbiology, 2018)
The olive-knot disease (Olea europea L.) is caused by the bacterium Pseudomonas savastanoi pv. savastanoi (PSV). PSV in the olive-knot undergoes interspecies interactions with the harmless endophyte Erwina toletana (ET); PSV and ET co-localize and form a stable community resulting in a more aggressive disease. PSV and ET produce the same type of the N-acylhomoserine lactone (AHL) quorum sensing (QS) signal and they share AHLs in planta. In this work we have further studied the AHL QS systems of PSV and ET in order to determine possible molecular mechanism(s) involved in this bacterial inter-species interaction/cooperation. The AHL QS regulons of PSV and ET were determined allowing the identification of several QS-regulated genes. Surprisingly, the PSV QS regulon consisted of only a few loci whereas in ET many putative metabolic genes were regulated by QS among which several involved in carbohydrate metabolism. One of these loci was the aldolase-encoding gene garL, which resulted to be essential for both co-localization of PSV and ET cells inside olive knots as well as knot development. This study further highlighted that pathogens can cooperate with commensal members of the plant microbiome.